Electronic Properties of Heterostructures of 2D Materials: An Ab-Initio Study - Hadadi, Wafa (Université d'Ottawa / University of Ottawa, 2020)
Researchers have recently become interested in two-dimensional materials such as graphene, hexagonal boron nitride (h-BN), Transition Metal Dichalcogenides (TMDs), etc. Their 2D hexagonal structures result in unique properties, which make these materials attractive for scientists and engineers. In this work, we investigated the electronic properties of graphene, h-BN, and MoS2 based on density functional theory (DFT). We first studied the electronic properties of monolayers of different materials. We found a zero bandgap and observed massless Dirac Hamiltonian in graphene. For h-BN, a large bandgap at K-point was observed. Also, we observed the bandgap opening in MoS2 and a strong splitting of its bands. Then, we extended these studies to graphene and h-BN bilayers. For graphene bilayer, we observed a gapless material and massive Dirac fermions. For h-BN bilayer, an indirect bandgap was observed, smaller in comparison with its monolayer. The main focus of this study was the investigation of graphene/h-BN heterostructures for different stacking configurations. The suitability of h-BN as a substrate for graphene is due to its small lattice constant mismatch with graphene and its high insulating gap (~ 5 eV). Another important aspect to be observed in graphene/h-BN heterostructures is the gap opening brought by the h-BN layer proximity to the initially gapless graphene layer. We found the effect of bandgap opening in graphene/h- BN and determined the most stable configuration which is the AB[CB]. This work supports the findings of many researchers who demonstrate that graphene/h-BN heterostructures are very useful as building blocks for nanodevices with desirable electronic properties.
Keywords: Heterostructures; Two-dimensional materials